Implementasi Kebijakan Sertifikasi Bendahara di Kantor Pelayanan Perbendaharaan Negara Medan II - Asnal Lubis; Badaruddin Badaruddin; Nina Siti Salmaniah Siregar (PERSPEKTIF, 2021)
This study aims to analyze the implementation of the treasurer certification policy in the APBN management work unit at KPPN Medan II. This study uses a qualitative approach where the researcher is the key instrument, the data collection technique is trangulation (observation, interviews, and documentation), the data obtained tend to be qualitative data, the data analysis is qualitative, and the results of qualitative research are to understand the meaning and construct phenomena. implementation of the treasurer certification policy. The results of the study indicate that the implementation of the treasurer certification policy has not yet reached the ideal condition, namely the achievement of all certified treasurers no later than 4 years since Presidential Regulation Number 7 of 2016 concerning Certification of Treasurers of the State Budget Management Work Unit comes into force. This is due to inconsistencies in policy implementation due to the non-compliance of the Head of the Work Unit in fulfilling the commitments in the Statement of Ability for the Treasurer to take the treasurer certification at the first opportunity. In addition, the incentive indicator is also one of the inhibiting factors for treasurers from participating in treasurer certification because treasurers feel that the workload, risks, and responsibilities are not balanced with the rewards received and the treasurer's career path is unclear.